Analisis Faktor - Faktor Sikap Kemandirian Anak Usia 4-5 Tahun di PAUD Khairin Kids T.A 2023/2024 - Citra Aulia Fitri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
If independence is the ability to think, feel, and do something on an impulse yourself based on the obligation in kehidupuan sehari-hari without relieved by someone else.The independence of a child may be improved through improving confidence children. Learning environment, usage method of pembiasaan, motivation, active participation of a child, and cooperation.This study attempts to analyze the independence of children aged faktor-faktor 4-5 years in early childhood khairin kids t.a 2023 / 2024.The research is descriptive qualitative research.The population research is students paud khairin kids of 12 students.Data collection techniques with sheets of observation and documentation. Based on the research kids are to respond to the independence with bai kapa delivered by teachers. As he walks into class unaccompanied parents, and putting a bekalnya without the aid of his teacher, wearing shoes and socks own, can go to the bathroom without the aid of teachers, smoothing stationery and understand and will of its own goods.